Air pressure measurement of circular thin plate using optical fiber multimode interferometer. (September 2021) - Bai, Yufang; Zeng, Jie; Huang, Jiwei; Yan, Zhenfeng; Wu, Yaxing; Li, Kaiyu; Wu, Qiang; Liang, Dakai
Highlights: Air pressure measurement based on SMS sensor is proposed and experimentally demonstrated. The SMS sensor modulates the wavelength and intensity of its transmission spectrum. The pressure sensitivity is − 0.069 dB/kPa and − 24.2 pm/kPa in the range of 0–60 kPa. The pressure sensitivity is − 0.2718 dB/kPa and − 106.7 pm/kPa in the range of 70–130 kPa. The pressure sensor can be applied for high precision measurement of low pressure. Abstract: In this paper, a simple singlemode-multimode-singlemode (SMS) optical fiber sensor is proposed and investigated for measuring the air pressure of a circular thin plate. Theoretical analysis and experimental demonstration are presents in this paper. The air pressure changes the strain and bending radius of the SMS sensor directly attached to the thin plate, and hence leads to shifts and intensity variation of the transmission spectrum. The relationship between transmission spectrum and pressure has studied by finite element method and optical simulation analysis. Experimental results show that the intensity-pressure and wavelength-pressure are − 0.2718 dB/kPa and −106.7 pm/kPa in a pressure range of 70–130 kPa, respectively. The repeatability of the sensor is good, and the hysteresis rate is low. The key features of the proposed sensor are its simple structure and manufacturing process, low manufacturing cost. It can be used for high-precision pressure measurement.